Molecular regulation of prostate cancer by Galectin-3 and estrogen receptor - Souza, Deborah Simão; Macheroni, Carla; Pereira, Gustavo José Silva; Vicente, Carolina Meloni; Porto, Catarina Segreti (Frontiers in Endocrinology, 2023)
Prostate cancer remains the most prevalent cancer among men worldwide. This cancer is hormone-dependent, so androgen, estrogen, and their receptors play an important role in development and progression of this disease, and in emergence of the castration-resistant prostate cancer (CRPC). Galectins are a family of β-galactoside-binding proteins which are frequently altered (upregulated or downregulated) in a wide range of tumors, participating in different stages of tumor development and progression, but the molecular mechanisms which regulate its expression are still poorly understood. This review provides an overview of the current and emerging knowledge on Galectin-3 in cancer biology with focus on prostate cancer and the interplay with estrogen receptor (ER) signaling pathways present in androgen-independent prostate cancer cells. We suggest a molecular mechanism where ER, Galectin-3 and β-catenin can modulate nuclear transcriptional events, such as, proliferation, migration, invasion, and anchorage-independent growth of androgen-independent prostate cancer cells. Despite a series of achievements in targeted therapy for prostate cancer, CRPC may eventually develop, therefore new effective drug targets need urgently to be found. Further understanding of the role of Galectin-3 and ER in prostate cancer will enhance our understanding of the molecular mechanisms of prostate cancer development and the future treatment of this disease.